Risks in banks and its impact on volatility of market returns: an empirical approach. (2018) - Singh, Prakash; Kumar, Sukriti
Banks have an extremely critical function in the process of financial intermediation by acting as engines of economic growth and in doing so they actively manage the various risks they are exposed to. During the periods of slowdown in the economy, it becomes important to identify how banks' operations affect their total risks so as to avoid any major crisis. The study tries to capture the different kinds of risks which a bank is exposed to and then relate it to volatility in the returns to shareholders of the bank. Accounting ratios have been used as a proxy for measuring the various categories of risks. Standard deviation of return on equity is used as a proxy for total risk. This total risk is then regressed against the accounting ratios so as to identify the important sources of total risk. Allowance for loan loss ratio, loan to asset ratio, total investment which is not held till maturity to total assets come out to be statistically significant variables explaining the volatility of return to equity in the study.